Оцінка рівня внутрішньої соціальної відповідальності підприємства - Kravchuk, Iryna («Видавничий дім «Гельветика», 2022)
he relevance of research on the socially responsible economic activity of Ukrainian business is exacerbated by the fact that the domestic economic environment has not passed in its historical development the necessary stages, which in Western society have led to an awareness of the importance of the philosophy of social responsibility. More obvious is becoming the fact that the reputation of domestic companies is increasingly dependent not only on their profitability, share value, and product qual-ity but also on their activity in the field of social responsibility. However, different approaches to the understanding of social responsibility, inconsistency of actions, and lack of purposeful assessment and management mechanisms provide an unstable platform for further implementation of social responsibility principles in the overall strategy of an enterprise. The purpose of this articleis to justify the need to present indicators of social responsibility in the financial statements of enterprises, as well as to deepen the methodological principles and develop practical recommendations regarding the provisioning of a system for as-sessing the strategic development of an enterprise on the basis and principles of social responsibility. The article uses economet-ric methods that were used to build models of an integrated approach to assessing the social responsibility of the food industry enterprises. It has been found that social responsibility is a vital component of the sustainable functioning of enterprises and is one of the strategic priorities of their development in the long term. The study showed that the need to implement the paradigm of social responsibility in the activities of domestic business structures for sustainable development and recovery from the socio-economic crisis can be resolved by methodological support for assessing the level of social responsibility of enterprises, which involves a combination of qualitative and quantitative indicators of assessment, determined by expert method and evaluated with a scoring method, with the identification of specific sectoral indicators of social responsibility, typical for the food industry enterprises, and the definition of its mandatory and voluntary levels.
ASSESSMENT OF THE LEVEL OF INTERNAL SOCIAL RESPONSIBILITY OF AN ENTERPRISE
Keywords: social responsibility; social partnership; socialization of an enterprise; indicators of social responsibility; indica-tors of the level of social responsibility